Proximal femoral replacement in non-neoplastic revision hip arthroplasty: five-year results. (11th March 2022) - Syam, Kevin; Unnikrishnan, P. Nithin; Lokikere, Naveen K.; Wilson-Theaker, William; Gambhir, Anil; Shah, Nikhil; Porter, Martyn
Abstract : Aims: With increasing burden of revision hip arthroplasty (THA), one of the major challenges is the management of proximal femoral bone loss associated with previous multiple surgeries. Proximal femoral arthroplasty (PFA) has already been popularized for tumour surgeries. Our aim was to describe the outcome of using PFA in these demanding non-neoplastic cases. Methods: A retrospective review of 25 patients who underwent PFA for non-neoplastic indications between January 2009 and December 2015 was undertaken. Their clinical and radiological outcome, complication rates, and survival were recorded. All patients had the Stanmore Implant – Modular Endo-prosthetic Tumour System (METS). Results: At mean follow-up of 5.9 years, there were no periprosthetic fractures. Clearance of infection was achieved in 63.6% of cases. One hip was re-revised to pseudo arthroplasty for deep infection. Instability was noted in eight of the hips (32%), of which seven needed further surgery. Out of these eight hips with instability, five had preoperative infection. Deep infection was noted in five of the hips (20%), of which four were primarily revised for infection. One patient had aseptic loosening of the femoral component and awaits revision surgery. The Kaplan-Meier survivorship free of revision of any component for any reason was 72% (95% confidence interval (CI) 51.3% to 92.7%), and for revisions of only femoral component for any reason was 96% (95% CI 86.3% to 105.7%) at five years. Conclusion: Dislocation and infection remain the major cause for failure, particularly in patients with pre-existing infection. The use of dual mobility cups, silver-coated implants, and less aggressive postoperative rehabilitation regimens would possibly aid in the reduction of complications. PFA performed in patients with periprosthetic fracture seem to fair better. This study supports the judicious use of PFA in non-oncological revision hip arthroplasties, and that they be performed by experienced revision arthroplasty surgeons. Cite this article: Bone Jt Open  2022;3(3):229–235.